Including older rural adults in research: Practical guidance for addressing the NIH Inclusion Across the Lifespan policy. Issue 5 (13th October 2020) - Croff, Raina; Gowen, L. Kris; Lindauer, Allison; Shofner, Sabrina; Brown, Kim; Eckstrom, Elizabeth
Abstract: Introduction: The NIH Inclusion Across the Lifespan policy has implications for increasing older adult (OA) participation in research. This study aimed to understand influential factors and facilitators to rural OA research participation. Methods: Thirty-seven rural adults aged ≥66 years participated in focus groups in community centers in four Oregon "non-metro" counties. Transcribed discussions were coded using open-axial coding by an interdisciplinary analytical team. Results: Ages were 66–96 (mean 82.2) years. Majority were women (64%) and white (86%). Primary, interrelated discussion themes were Motivation and Facilitators, Perceptions of Research, and Barriers to Research Participation. Participants were motivated to engage in research because they believed research had implications for improved longevity and quality of life and potentially benefited future generations. Motivational factors influencing participation included self-benefit and improving others' lives, opportunities to socialize and learn about current research, research transparency (funding, time commitment, and requirements), and financial compensation. Perceptions influencing trustworthiness in research included funding source (industry/non-industry) and familiarity with the research institution. Barriers to research participation included transportation and concern about privacy and confidentiality. Suggestions for making research participation easier included researchers coming to rural communities and meeting participants in places where OAs gather and providing transportation and hotel accommodations. Conclusion: Lessons learned offer practical guidance for research teams as they address the new NIH Inclusion Across the Lifespan policy. Including OAs in research in ways that motivate and facilitate participation will be critical for a robust representation across the lifespan and in tailoring treatments to the specific needs of this population.